A Systems Approach to Studying Online Communities - Jeremy Foote (Media and Communication, 2022)
Much early communication research was inspired by systems theory. This approach emphasizes that individuals and groups use communication to interact with and respond to their larger environment and attempts to outline the ways that different levels interact with each other (e.g., work groups within departments within firms). Many concepts from systems theory—such as emergence and feedback loops—have become integral parts of communication theories. However, until recently, quantitative researchers have struggled to apply a systems approach. Large-scale, multilevel trace data from online platforms combined with computational advances are enabling a turn back toward systems-inspired research. I outline four systems-based approaches that recent research uses to study online communities: community comparisons, individual trajectories, cross-level mechanisms, and simulating emergent behavior. I end with a discussion of the opportunities and challenges of systems-based research for quantitative communication scholars.